Pembuatan Dokumentasi HACCP di Plant-1 PT X - Megawati, Maria Yohana; -, Felecia (Jurnal Titra, 2013)
PT X is one of coconut oil company in Indonesia with copra and Crude Palm Oil (CPO) as raw material.Â  PT X has ISO 9001:2008 certification, and now they want to get ISO 22000:2005 certification to gain customer satisfaction. One of ISO 22000:2005 requirement is certification of HACCP. This thesis intended to prepare HACCP at Plant-1 PT X. This preparation have been done until making of HACCP team, product description, making of flowchart, making of principle one until principle seven of HACCP. Result of this thesis has been done until making follow up steps for every Critical Control Point (CCP). Problems that occurs in CCPÂ  are metal, oil and grease may contaminate coconut oil. Suggestions that given for these problems are oil and grease must be changed into food grade oil and grease and application of metal trap. Result of implementation that has been done is given metal trap for every section that highly risk contaminated by metal.